A Confessional Representation of Ethnographic Fieldwork in an Academy Sport Setting. (October 2021) - Bowles, H.C.R.; Fleming, S.; Parker, A.
Methodological "confessions" are an established genre of ethnographic writing and have contributed to the development of reflexivity in the practice of qualitative research. Yet despite their prevalence, methodological reflections on the specific challenges of conducting ethnography in institutional sport settings have not been developed. The aim of this article, therefore, is to provide a confessional representation of ethnographic fieldwork in a male academy sport environment in the United Kingdom which exhibited several institutional characteristics. Five images are used as stimuli for further methodological reflection in order to illustrate and analyze some practical, ethical, and relational qualities of ethnographic fieldwork. The interpretation and analysis draw attention to strategic ways ethnographers adapt their ethnographic presence in response to specific contextual challenges and constraints. The article concludes with a series of recommendations to guide ethnographic fieldworkers (especially novice ethnographers) in settings of a similar nature.